Financial and critical analysis of vendors management in Banglalink Telecommunication Ltd. - Moinuddin, Ferdous Lamisa (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2015.